2018
DOI: 10.26480/mjhr.01.2018.03.09
|View full text |Cite
|
Sign up to set email alerts
|

OCCURRENCE, DISTRIBUTION, HOST PREFERENCE AND DAMAGE SEVERITY OF RED PUMPKIN BEETLE- A Review

Abstract: The red pumpkin beetle has been found to be widely distributed throughout all zoogeographic regions of the world except the Neoarctic and Neotropical regions and all over the SouthEast Asia, Africa, Mediterranean region towards the west and Australia in the East. It was also found to occur in Bangladesh,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Therefore, it is imperative to invest in developing adaptive industrial wastewater treatment technologies to sustain water supply, healthier environments and industrial development (Shamsuddin et al, 2017). Common pollutants in petrochemical industry discharges are organics, particularly petroleum hydrocarbons (Biswas, 2018;Khan, 2018). Therefore, wastewater from petrochemical industries often require a combination of treatment methods to remove oil and other contaminants before discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to invest in developing adaptive industrial wastewater treatment technologies to sustain water supply, healthier environments and industrial development (Shamsuddin et al, 2017). Common pollutants in petrochemical industry discharges are organics, particularly petroleum hydrocarbons (Biswas, 2018;Khan, 2018). Therefore, wastewater from petrochemical industries often require a combination of treatment methods to remove oil and other contaminants before discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The main effective components of Ginkgo leaf extracts are flavonoid and lactone compounds (Chen et al, 2008;Nazihah et al, 2018). Flavonoid is a kind of natural antioxidant which has broad-spectrum antibacterial and antimicrobial properties (Huo et al, 2012;Nordin et al, 2018;Khan, 2018), so as a new kind of natural preservative, Ginkgo leaf extracts has great potential. In the past, the study of Ginkgo biloba leaf mainly focused on the research on the value of medicinal care, however studies on fruit preservation is meagre (Feng et al, 2013;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on marsh wetland have demonstrated that interannual variation of water vapor flux is caused by temperature influence on ecosystem; and water vapor flux of marsh wetland is mainly affected by net radiation (Goulden, 2007;Sun, 2008;Dhami et al, 2018). Further, observation on water vapor flux of peatland found that daily and seasonal variations were in single peak curves, and variation was mainly affected by both the radiation and vapor pressure difference (Peng, 2007;Khan, 2018). Currently a lot of research has been carried out on water vapor flux in wetland ecosystem, but not much on riverside wetland ecosystem in cold regions.…”
Section: Introductionmentioning
confidence: 99%